The Effect of Corporate Social Responsibility on The Welfare of The Surrounding Community at PT. Vale Indonesia TBK - Elsa Sartika; Herlina Sakawati; Muh. Rizal S (Public Resource Innovation Management and Excellence, 2025)
This study examines the influence of corporate social responsibility on the welfare of the surrounding community at PT. Vale Indonesia Tbk. The purpose of this study was to determine of corporate social responsibility at PT. Vale Indonesia Tbk, to determine the level of welfare of the surrounding community at PT. Vale Indonesia Tbk, and to find out the influenceof corporate social responsibility on the welfare of the surrounding community at PT. Vale Indonesia Tbk. This research approach is quantitative. This research was conducted at PT. Vale Indonesia Tbk, namely Malili District, East Luwu Regency which is a sub-district area directly affected by the company's operations. The source of data in this research is the surrounding community at PT. Vale Indonesia Tbkfrom November to December 2023. The sample used was 100 people. Data collection techniques in the form of observation, questionnaires, and documentation. Data analysis techniques include validity test, reliability test, normality test, descriptive analysis, simple linear regression analysis, correlation coefficient analysis, and coefficient of determination analysis. The results of the study show that the indicators used for each of these variables indicate where of corporate social responsibility is in the very good category. Indicators on the community welfare variable are in the very good category. Based on the test of the determinant coefficient, the influence is very strong between the two variables. So it was concluded that the influence of corporate social responsibility on the welfare of the surrounding community at PT. Vale Indonesia Tbk is very strong.